Importance of leadership in work teams - Alatrista Oblitas, Graciela Ivonne (2020)
Currently teamwork in a team has been one of the most important factors in a company to achieve its goals. It is even considered that being willing to work in a team is more important than academic training or experience, because promoting a good environment results in the team being motivated and highly committed additionally they will learn to propose their ideas with total freedom giving space for the mill to emerge frequently as a way to give solutions or offer new proposals. Therefore, it is vital that the leader considers at all times the abilities of each of the members, in addition to maintaining enthusiasm by letting them know permanently that each of them is an important part. To achieve this, it is crucial that the leader brings value, so that the team wants to do its best and show its best version.